Comparison of 19- and 22-gauge needles in EUS-guided fine needle aspiration in patients with mediastinal masses and lymph nodes - Necla OSMANOĞLU; Yıldıran SONGÜR; Sema BİRCAN and Nilgün KAPUCUOĞLU (Turkish Journal of Gastroenterology, 2019)
-